Lao People's Democratic Republic - Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
Lao P.D.R.’s risks of external and overall debt distress continue to be assessed as high. Under the revised low-income country debt sustainability framework (LIC DSF), its debt carrying capacity has deteriorated and most external and total public debt indicators breach their respective indicative thresholds and benchmarks under the baseline scenarios. External debt indicators are most vulnerable to shocks to exports and depreciation of the currency. Public and external debt indicators are most sensitive to the contingent liabilities shock, while recent natural disasters underscore the need for strengthening buffers. The low level of reserves adds to these vulnerabilities. Factors, such as the large share of electricity export earnings under long-term intergovernmental power purchase agreements, and a strong and growing electricity exports market help mitigate risks, keeping the debt outlook sustainable. Market access is being maintained, around 65 percent of external debt is concessional, and the stock of expenditure arrears is declining. Rebuilding fiscal space, adopting clear guidelines for sovereign debt issuance and guarantees, assessing risks from contingent liabilities, and improving debt management are immediate priorities. Assessing and targeting infrastructure projects with high growth and social returns and financing these with concessional financing would benefit debt sustainability. Strengthening the business environment and governance, would improve the investment outlook, help diversify and make growth more inclusive. Increasing the export base, continuing to maximize the proportion of concessional loans and improving primary deficits would help to keep the debt burden contained.